2004
DOI: 10.1007/bf02708482
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation and atomic force microscopy measurements on reactively sputtered TiN coatings

Abstract: Titanium nitride (TiN) coatings were deposited by d.c. reactive magnetron sputtering process. The films were deposited on silicon (111) substrates at various process conditions, e.g. substrate bias voltage (V B ) and nitrogen partial pressure. Mechanical properties of the coatings were investigated by a nanoindentation technique. Force vs displacement curves generated during loading and unloading of a Berkovich diamond indenter were used to determine the hardness (H) and Young's modulus (Y) of the films. Detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Coatings prepared at low bias voltages are characterized by coarse grains with high density of defect structure and contain dislocations over grain boundaries [27]. On increasing the bias voltage, grain structure refinement, along with the high compressive stress induction in the TiAlC coatings, cause subsequent increase in the hardness [27]. Wang et al reported similar results for nc-TiC coatings [26].…”
Section: Hardness Measurementmentioning
confidence: 73%
See 2 more Smart Citations
“…Coatings prepared at low bias voltages are characterized by coarse grains with high density of defect structure and contain dislocations over grain boundaries [27]. On increasing the bias voltage, grain structure refinement, along with the high compressive stress induction in the TiAlC coatings, cause subsequent increase in the hardness [27]. Wang et al reported similar results for nc-TiC coatings [26].…”
Section: Hardness Measurementmentioning
confidence: 73%
“…The trend observed in H and E* is attributed to grain size refinement and compressive stress induction [26]. Coatings prepared at low bias voltages are characterized by coarse grains with high density of defect structure and contain dislocations over grain boundaries [27]. On increasing the bias voltage, grain structure refinement, along with the high compressive stress induction in the TiAlC coatings, cause subsequent increase in the hardness [27].…”
Section: Hardness Measurementmentioning
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the results of Wang et al [17], for the trend observed in hardness and Young's modulus that was attributed to grain size refinement and compressive stress induction. Increases in the substrate RF bias, grain structure refinement, along with the high compressive stress induction in the CrAlSiN films, lead to increased hardness [18]. Fig.…”
Section: Properties Of Cralsin Filmsmentioning
confidence: 96%
“…These coatings have also shown their ability to improve the corrosion resistance of a variety of steel substrates (William Grips et al 2006). Addition of Al into TiN (or CrN) has been shown to improve the oxidation resistance of transition metal nitrides considerably (Barshilia and Rajam 2004a;Barshilia et al 2005. The structure and properties of TiN have been studied in detail by several researchers.…”
Section: Introductionmentioning
confidence: 99%